The Effect of Intrinsic Motivation and Work Engagement on Contextual Performance - Hoxha, Sejdi; Ramadani, Riad (Migration Letters, 2024)
Employee motivation and engagement are critical to achieving maximum productivity at work. The aim of this research is to determine the impact of employees’ intrinsic motivation and engagement on contextual performance. The research participants are employees from two public companies in Kosovo. The data were gathered using the convenient sampling method, with 315 employees working in various positions. The study variables were tested through correlation and hierarchical regression analyses. The study found that intrinsic motivation improves contextual performance. In terms of the impact of intrinsic motivation on work engagement, the findings discovered that autonomy and competence have a positive effect on vigor and dedication, as well as competence has a substantial favourable effect on absorption. Furthermore, when the effect of work engagement on contextual performance was investigated, the results found that engagement had a highly significant effect.